How can I help? A less-is-more-approach to responsible, supportive and sustainable, doctoral supervision - Jessica Enevold Duncan (Högre Utbildning, 2024)
The significance of writing for PhD students, particularly at faculties of Humanities, cannot be overemphasized; the written manuscript is the final product to be publicly discussed by external examiners. This article takes as its starting point a “quick & dirty” study of a student-initiated writing group at a humanities department (HD) and the assumption that thesis supervisors nowadays need to take more responsibility for doctoral students’ writing because of existing demands on PhD-students to publish or perish and finish on time (Brodin, 2020). It asks the question how, in times of stress and demands on productivity, increased responsibility may be practiced sustainably in terms of work-load and still benefit students’ development and goals. In other words: How can I, as supervisor, help? What support is needed and how much?